Preparation, Characterization and Application of Cyclodextrin‐Containing UV‐Curable Waterborne Polyurethane Based on Guest Regulation. Issue 7 (17th February 2020) - Yao, Sa; Shi, Jun; Du, Xiangxiang; Lu, Maoping; Liu, Yingchun; Liang, Liyan; Lu, Mangeng
Abstract: A novel UV‐curable supramolecular waterborne polyurethane (PU) was prepared through the introduction of methylated‐β‐cyclodextrin (Me‐β‐CD). The host‐guest interactions between Me‐β‐CD and photosensitive monomer (PM) were further investigated by 1 HNMR and fluorescence spectroscopy, where the corresponding equilibrium constant was also calculated. Compared with pure PU, the tensile strength and thermal stability of UV‐curable PU films increased evidently. Furthermore, cotton fabrics treated by PU were obtained via soaking method. To further construct a 3D cross‐linked network, the UV‐curable technique was applied by adopting PM with different amounts of the unsaturated bond, which could provide cotton fabrics with different functionalities. The results show that the higher amount of unsaturated bond, the better water repellency which cotton fabrics own. What's more, the water repellency of the waterborne polyurethane fabric obtained by the host‐guest inclusion was larger than that of the physical mixture. Those provide a strategy for synthesizing functional PU based on guest regulation, which can be applied for fabric finishing. Abstract : The UV‐curable supramolecular waterborne polyurethane (PU) was successfully synthesized through the introduction of methylated‐β‐cyclodextrin (Me‐β‐CD). All test characterizations illustrate the mechanical and water resistance of PU fabric obtained by the host‐guest inclusion was larger than that of the physical mixture.